2022
DOI: 10.1364/optica.443440
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast magnetic scattering on ferrimagnets enabled by a bright Yb-based soft x-ray source

Abstract: We demonstrate the first time-resolved X-ray resonant magnetic scattering (tr-XRMS) experiment at the N edge of Tb at 155 eV performed using a tabletop high-brightness high-harmonic generation (HHG) source. In contrast to static X-ray imaging applications, such optical-pump-X-ray-probe studies pose a different set of challenges for the ultrafast driver laser because a high photon flux of X-rays resonant with the N edge must be attained at a low repetition rate to avoid thermal damage of the sample. This labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 83 publications
(53 reference statements)
1
8
0
Order By: Relevance
“…As already suggested by Carva [22], "correctly" probing the magnetization might thus require an integration over the entire MCD spectrum (as intrinsically performed using broadband sources), and must be critically discussed in femtomagnetism experiments, where single, well-defined probing wavelengths are used [22]. This could explain why several studies, despite using comparable experimental conditions, reported rather different characteristic demagnetization times [41][42][43] and significant differences concerning the onset of demagnetization in material systems composed of multiple elements [44][45][46].…”
Section: Discussionmentioning
confidence: 98%
“…As already suggested by Carva [22], "correctly" probing the magnetization might thus require an integration over the entire MCD spectrum (as intrinsically performed using broadband sources), and must be critically discussed in femtomagnetism experiments, where single, well-defined probing wavelengths are used [22]. This could explain why several studies, despite using comparable experimental conditions, reported rather different characteristic demagnetization times [41][42][43] and significant differences concerning the onset of demagnetization in material systems composed of multiple elements [44][45][46].…”
Section: Discussionmentioning
confidence: 98%
“…Attosecond pump-probe spectroscopy has emerged as a useful tool for probing and controlling ultrafast electronic dynamics in atoms [1][2][3][4][5][6][7][8][9][10][11][12][13][14], molecules [15][16][17][18][19][20][21][22], and condensed matter [23][24][25]. Above the ionization threshold, the electronic continuum of polyelectronic atoms and molecules feature localized states that are only transiently bound, since they can relax by Auger decay.…”
Section: Introductionmentioning
confidence: 99%
“…Extending the bright photon energy range of HHG is important for many applications in science and technology: First, bright and broadband soft x-ray radiation spans many element-specific absorption edges, e.g., the "water-window" energy, and enables table-top element-resolved spectroscopy and microscopy (13)(14)(15). Second, broader HHG bandwidths can support the generation of shorter attosecond pulses (16,17) or powerful broadband imaging and spectroscopy methods (18).…”
Section: Introductionmentioning
confidence: 99%